A century of macroeconomic and monetary thought at the National Bank of Belgium - Ivo Maes (National Bank of Belgium, 2010)
"A century of macroeconomic and monetary thought at the National Bank of Belgium" traces the history of economic research at the National Bank of Belgium, from the early decades of the 20th century to its present functioning in the Eurosystem. The study also goes into the major economic policy debates, as well as the specific lines of macroeconomic and monetary thinking at the National Bank of Belgium. The focus is very much on the role of the Research Department in policymaking and its dialogue (and debates) with the academic community
Keywords: A11; B22; E42; E58; N10; 330; National Bank of Belgium; central banking; monetary theory; economic research; Zentralbank; Geldtheorie; Makroökonomik; Geldpolitik; Wechselkurspolitik; Wirtschaftswissenschaft; Belgien